(untitled) (Global Journal of Human-Social Science, 2014)
This paper looks at the spirit of social service or seva in four popular contemporary Hindu Inspired Faith Movements (HIFMs) of Indian origin now having a global presence. These include Chinmaya Mission, Vivekananda Kendra, Mata Amritanandamayi Mission and Art of Living. The core questions which this paper addresses are: a) how seva as a mandate originated in these HIFMs b) what in the seva is volitional, what are the prescribed aspects and doctrines c) how tangible seva initiatives interface with various systems and d) how seva contributes to institution building through the interplay of memory and oblivion dynamics thereby evolving the style of HIFMs. This paper argues that seva becomes a pillar of institution building for HIFMs. It operationally stems from volition, prescriptivism and doctrinaire propositions given by the HIFMs. The scope encompasses the core social sectors which then projects the HIFMs assertion/partnership in development goals in a resource limited setting. The styles of seva go beyond simple instilling/extolling of virtues, but rather portray as vanguards of fulfilling social obligations and perpetuating the charismatic teacher and Hindu based memories. With the Hindu inspiration as non-negotiable, the operational form contains communitarian notions of social citizenship and social justice. There is an element of ’public good’ factoring in the HIFMs ideals.